Convergence analysis of a one-step intermediate newton iterative scheme (2001)
We study a one-step intermediate_method for the iterative computation of a zero of the sum of two nonlinear operators. The proposed method contains Newton scheme and the Modified Newton scheme as special cases and therefore provides a unified setting for the study of both methods.